Level of exposure to X-Ray in security gates of Tehran's Imam Khomeini airpor - Firouz Valipour; Hossein Kardan Yamchi; Gholamhossein Pourtaghi; Habibollah Dehghan; Mohammad Salem (Gonabad University of Medical Sciences, 2017)
X-Ray is an ionizing electromagnetic radiation with a wide spectrum. A setting where this radiation is widely used is airport security units. This study was conducted to measure the level of momentary exposure to X-Ray in operators and personnel working in security gates of Imam Khomeini airport. In this cross-sectional study, the X-Ray machines used in security gates of Imam Khomeini airport are HEIMANN. The radiation was measured in both men's and women's inspection units, with curtain down and curtain up when passengers' luggage coming out of the machine, around the machine, operators' seat located half a meter and one meter from the machine. The X-Ray was measured using smartlon. The results were analyzed using t-test, and level of X-Ray was compared to occupational standard limit of American conference of governmental industrial hygienists, 25 μsvh-1. Total mean of X-Ray measured in different positions of HEIMANN machine was 1.02 μsvh-1 ± 0.9032 μsvh-1. The X-Ray measured in men's and women's inspection units was 1.3025 μsvh-1 ± 0.985 μsvh-1 and 1.06 μsvh-1 ± 0.658 μsvh-1, respectively. The X-Ray measured in this study was compared to the occupational standard limit using t-test, which indicated a significant difference. Although level of X-Ray in all above cases was lower than the occupational standard limit, any contact with this ray even at low doses may cause complications in humans. Therefore, constant monitoring is essential for maintaining and improving health of airport security staff.